An Approach to Data Utilization of The Lokomat Rehabilitation Robot - Sapiee, M.R.; Marhaban, M.H.M.; Ishak, A.J.; Miskon, M.F. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
The use of exoskeleton robot worn on human body has been widely researched and some have been commercialized. Lower limb exoskeleton robot worn in parallel on human lower body has found many applications especially in the rehabilitation of human walking gait. It is used as a robotic therapy in assisting patient with walking difficulties to recover back his walking ability. Using Lokomat rehabilitation robot for therapy is not meant to guide the patient to walk only; but this robotic therapy system has the ability to record information signals during each therapy session. It is found out that less research and attention has been given on the methods that can utilize the recorded data which could be very useful and very informative for physiotherapy study. Thus, the objective of this paper is to highlight the method to utilize the recorded data from Lokomat physiotherapy session.